An Efficient Technique for Segmentation of Microarray Image and Analysis of Image by Using Genepix Software - Naga Durga Aravind, Dr. Saurabh Pal, Dr. D. Subbarao (International Journal of Advanced Science and Technology, 2020)
Microarray is very useful and vastly growing technology that helps in analyzing genetic data. Because of the advancement in this field there is lot of genetic data being produced everyday and these data are needed to be interpreted and analyzed properly to get accurate results. With the advancement in computer technologies and software, we now analyze microarray images by computers. There are many open sources as well as commercially available software that help us to analyze microarray images. Microarray image analysis can be divided into three stages-Addressing or Gridding of spots, Segmentation and finally Background and Foreground Intensity Extraction. This paper tries to compare few of the available microarray image analysis software on the basis of the above mentioned techniques used and also on the efficiency and ease of use of Genepix software.